Research on the Optimal Spacing of Urban Environmental Sanitation Facilities: Smoke-extinguishing Pillar as an Example. Issue 1 (December 2020) - Li, Yong; Zhou, Cheng; Lu, Haixiang; Xu, Han; Li, Gang
Abstract: Since the spacing of urban environmental sanitation facilities is not reasonable enough, customers and service desks in the queuing theory were used to simulate the environmental sanitation facilities and pedestrians in daily life, and the established queuing system was then optimized based on the purpose of minimum costs. This optimization model was used to determine the optimal spacing of the sanitation facilities for street-like linear sites, and quantify the positive and negative utility of whether garbage is thrown into the sanitation facilities. Moreover, the optimal spacing of the sanitation facilities on street-like linear places was calculated according to the coefficient "k" and the maximum tolerable distance "s" of pedestrians holding a piece of garbage. Moreover, an algorithm for park-like flat sites was provided by establishing a set covering model. Then the maximum tolerable distance of pedestrians holding a piece of garbage was obtained through field research, which was then used in practical calculation. Finally, conclusions and suggestions were given correspondingly.